UTILIZING TEXT-RESPONSIVE FORM TO ENHANCE 4TH-SEMESTER STUDENTS’ COMPREHENSION AND CRITICAL ENGAGEMENT WITH SCIENTIFIC ARTICLES - Ayubadiah, Fitrahnanda (Faculty of Letters Universitas Balikpapan, 2024)
This study aims to investigate the effectiveness of Text-Responsive Forms (TRFs) in enhancing the comprehension and critical thinking skills of 4th-semester students when engaging with scientific articles. The study employed a qualitative study approach, incorporating Text Responsive Form assessment, questionnaire, and semi-structured interviews to gather data on students’ written and oral responses. The findings revealed that while Text-Responsive Forms were successful in improving foundational comprehension, as students were able to accurately summarize and organize key points from the articles, they struggled with deeper critical engagement and analysis. Interviews revealed that many students could clearly articulate basic information but found it challenging to delve into more complex, analytical discussions. Students’ perceptions indicated that the Text Responsive Form was useful for structuring responses but still insufficient in fostering critical analysis. The study concluded that while Text Responsive Forms provide important foundational skills, they should be supplemented with additional strategies to better prepare students for academic and advanced writing tasks that require comprehensive understanding and critical evaluation of academic texts.